2006
DOI: 10.1007/s11274-005-9074-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of A Metal-resistant Pseudomonas Aeruginosa Strain

Abstract: The use of microorganisms to remove heavy metals from industrial effluent is an area of extensive research and development. Attempts have been made to isolate and characterize metal-resistant microorganisms from treated oil mill industry effluent wastewater samples. The metal-resistant organisms that showed values of minimum inhibitory concentration towards metals (Cd, Cr, Ni and Pb) ranging from 100 to 800 ppm level were screened. A potent metal-resistant organism, isolate BC15 from the wastewater samples was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 46 publications
6
35
1
Order By: Relevance
“…The inability to grow at higher concentration was associated with reduction in growth due to the metal binding capacity of CRB15 which resulted by means of interaction between metal cations and functional groups of the cell wall. Similar results were also reported by Friis and Myers-Keith (1986) and Raja et al (2006). …”
Section: Effect Of Cu On Bacterial Growthsupporting
confidence: 92%
See 1 more Smart Citation
“…The inability to grow at higher concentration was associated with reduction in growth due to the metal binding capacity of CRB15 which resulted by means of interaction between metal cations and functional groups of the cell wall. Similar results were also reported by Friis and Myers-Keith (1986) and Raja et al (2006). …”
Section: Effect Of Cu On Bacterial Growthsupporting
confidence: 92%
“…Growth rates of the strain CRB15 in the presence of heavy metals were consistently slower than that of control. Similar results were reported by Suresh Kumar et al (2001), Pal et al (2004) and Raja et al (2006).…”
Section: Resistance To Heavy Metalssupporting
confidence: 91%
“…on different concentrations of lead metal from 0.4 to 0.7g/l with consideration of incubation time and found that the growth increase (lag phase) until reach stationary phase at 360min. Growth pattern of P. aeruginosa strain BC15 on different concentrations of Cr, Ni, Pb and Cd metals was studied by Raja et al (2006). It was reported by different authors that the growth of the bacterial isolates is reduced as affected by the metals in higher concentrations comparing to the control (Suresh et al, 1998;Suresh et al, 2001 andPal et al, 2004).…”
Section: Phenotypic and Genotypic Identification Of The Bacterial Isomentioning
confidence: 99%
“…The characterization of rhizobacteria colonies based on the shape and colors of the colonies were examined under a microscope (Leica-DM 1000) [15,16]. Chemical tests of of Gram stain, calatalase, oxidase and motility were also performed.…”
Section: Bacteria Characterizationmentioning
confidence: 99%